Psychometric properties of the Portuguese teacher-version of the Inventory of Callous-Unemotional Traits in Preschoolers - Figueiredo, Patrícia (2023)
Abstract: Several authors suggest that Callous-Unemotional (CU) traits may be useful in identifying adolescents who exhibit initial, severe, chronic, and aggressive conduct problems. The Inventory of Callous-Unemotional Traits (ICU) was developed to assess these traits, later associated with psychopathy, in children and adolescents. This study aims to analyze the psychometric properties of the Portuguese version of the teacher-report ICU for preschool-age children. The sample was collected in public schools and comprised the responses of 46 preschool teachers concerning 131 children (62 girls) between 3 and 6 years of age. Results indicate that a two-factor model revealed the best fit to our data, including a Callous and an Uncaring factor, resorting to 12 of the original 24 items. Additionally, the results of this study also provide evidence of measurement invariance across sex for the ICU, allowing us to compare mean levels of CU traits between boys and girls. The results of the present study showed that the Portuguese version of the ICU scale (teacher’s version) seems reliable and valid for evaluating CU traits in preschool children.